Nitrogen Resorption and Nitrogen Use Efficiency in Cacao Agroforestry Systems Managed Differently in Central Sulawesi - TRIADIATI TRIADIATI; SOEKISMAN TJITROSEMITO; EDI GUHARDJA; SUDARSONO SUDARSONO; IBNUL QAYIM; CHRISTOPH LEUSCHNER (HAYATI Journal of Biosciences, 2007)
Cacao agroforestry is a traditional form of agriculture practiced by the people of Central Sulawesi. These agroforestry systems vary from a simple system following selective cutting of forest trees, to a more sophisticated planting design. The cacao was planted under remaining forest covers (CF1), under planted trees (CF2), and between shade trees Gliricidia sepium (CP). The objectives of this study were to quantify nitrogen use efficiency (N NUE) and nitrogen resorption in cacao agroforestry systems. The N NUE at the ecosystem scale (N NUEES) for the cacao agroforestry systems were compared with the natural forest. The results showed that CP produced the highest litterfall and cacao foliar nitrogen. CP and CF1 produced litterfall and the nitrogen resorption that not were significantly different. In contrast, CF2 produced the lowest litterfall, hence required lower nitrogen supply. The nitrogen resorption of CF2 was less than that of CF1 and CP. However, N NUE in cacao plant (N NUEC) of CF2 was higher than that of the CP. The N NUEES of either CF1 or CF2 were similar to that of the natural forest, but higher than that of the CP. Using shade trees in cacao plantations increased foliar nitrogen concentration, nitrogen resorption, N NUEC and N NUEES; thus, might be one reason for a higher productivity of cacao in unshaded systems. Key words: cacao agroforestry system, cacao foliar nitrogen, nitrogen resorption, N NUE